Building Tokyo by the Sea: Visions, strategies and projects on the edge of the water 1950-2020 - Pernice, Raffaele; Covatta, Alice; Zuccaro Marchi, Leonardo (International Planning History Society Proceedings, 2024)
Since the time it became the new de-facto capital of Japan with the name of Edo in early XVII century, modern Tokyo has kept a special relationship with its waterfronts and on several occasions the expansion of the city has been pursued by looking at the sea as potential new habitat for growth and development. At the dawn of 20th Century, and especially in the aftermath of the end of the Pacific War, bold architectural ideas and city planning schemes were proposed and enacted to convey a phase of unprecedented economic resurgence and urban sprawl articulated by an impressive process of infrastructure build-up and industrial modernization. Looking at the different stages of city development in the 70 years from 1950 to 2020s, the paper will shed light on several aspects of the process of urban development of the waterfronts of Tokyo during this period. It will provide a critical account of the transformation of the city and the various innovative visions, ideas and projects from the initial stage of economic boom of the 1960s and 1980s, to the end of the “Bubble” in the 1990s, and the phase of relative decline at the start of the New Millennium, until the current new phase of urban regeneration and new wave of large-scale urban development projects driven by new national ambitions in the context of the competition with other East Asian megacities.